Typological characterisation of vintage unreinforced masonry buildings of Queensland, Australia. (July 2022) - Khattak, Nouman; Derakhshan, Hossein; Thambiratnam, David P.; Perera, Nimal Jayantha
Abstract: Characterisation of buildings is critical for the rapid assessment and seismic loss estimation of buildings after an earthquake event. This paper presents a literature review on the characterisation of unreinforced masonry (URM) buildings followed by a typological study of the building stock in Queensland, Australia. The literature review showed that characterisation studies are aimed at cataloguing and developing inventories of buildings for the purpose of seismic vulnerability and risk assessment, and behaviour-influencing parameters are often used as a basis for building classification. Guided by the literature review, a field study was conducted to document important features of vintage (pre-1940) URM buildings that can influence their behaviour during an earthquake. The surveyed aspects included the construction year, number of storeys, roof type, irregularities in plan, isolated or inter-connected buildings, overall dimensions of the buildings, size and shape of windows, façade opening ratio, presence of chimneys, and the style of parapets. Importantly, it was found that certain parapet typologies are prevalent, but that their seismic behaviour is currently unknown. A few such typologies were recommended for future seismic assessment studies. This study can serve as a basis for conducting seismic assessment risk and vulnerability studies in the future.